2017 International Workshop on Pattern Recognition in Neuroimaging (PRNI) 2017
DOI: 10.1109/prni.2017.7981506
|View full text |Cite
|
Sign up to set email alerts
|

Automatic 1D convolutional neural network-based detection of artifacts in MEG acquired without electrooculography or electrocardiography

Abstract: Magnetoencephalography (MEG) is a functional neuroimaging tool that records the magnetic fields induced by electrical neuronal activity; however, signal from non-neuronal sources can corrupt the data. Eye-Blinks (EB) and Cardiac Activity (CA) are two of the most common types of non-neuronal artifacts. They can be measured by affixing eye proximal electrodes, as in electrooculography (EOG) and chest electrodes, as in electrocardiography (EKG), however this complicates imaging setup, decreases patient comfort, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…The results obtained from our model are comparable to recently published work of [44][45][46]. However, we have demonstrated that when temporal and spatial information are combined into one model the artifact rejection performance is increased (Figure 7).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The results obtained from our model are comparable to recently published work of [44][45][46]. However, we have demonstrated that when temporal and spatial information are combined into one model the artifact rejection performance is increased (Figure 7).…”
Section: Discussionsupporting
confidence: 89%
“…In their work, the neural networks are trained to classify ECG and EOG related artifact components from the timeseries of the ICs. In a related study, the same authors showed automatic detection of EOG related components using a spatial representation of the independent components [44]. As a part of their conclusions they suggest a neural network which combines both temporal and spatial information, which is ideal.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…To guarantee HRV could reflect task-related state more precisely, ECG record was directly collected from the MEG raw data under the go/no-go task after ICA (36). There were two reasons to choose time domain analysis.…”
Section: Hrv Data Acquisition and Analysismentioning
confidence: 99%